Leishmania infection-derived extracellular vesicles drive transcription of genes involved in M2 polarization - Emerson, Lisa E.; Gioseffi, Anna; Barker, Hailey; Sheppe, Austin; Morrill, Julianne K.; Edelmann, Mariola J.; Kima, Peter Epeh (Frontiers in Cellular and Infection Microbiology, 2022)
Although it is known that the composition of EVs is determined by the cell’s characteristics and its environment, the effects of intracellular infection on EV composition and functions are not well understood. We had previously shown that cultured macrophages infected with Leishmania parasites release EVs that contain parasite derived molecules (LiEVs). In this study we show that LdVash, a molecule previously identified in LiEVs from L. donovani infected RAW264.7 macrophages is widely distributed in the liver of L. donovani infected mice. This result shows for the first time that parasite molecules are released in EVs and distributed in infected tissues where they can be endocytosed by cells in the liver, including macrophages that undergo a significant increase in numbers as the infection progresses. To commence evaluating the potential impact of LiEVs on macrophage functions, we show that primary peritoneal exudate macrophages (PECs) express transcripts of signature molecules of M2 macrophages such as arginase 1, IL-10 and IL-4R when incubated with LiEVs. In comparative studies that illustrate how intracellular pathogens control the composition and functions of EVs released from macrophages, we show that EVs from RAW264.7 macrophages infected with Salmonella enterica serovar Typhimurium activate PECs to express transcripts of signature molecules of M1 macrophages such as iNOS, TNFα and IFNγ and not M2 signature molecules. Finally, we show that in contrast to the polarized responses observed in in vitro studies of macrophages, both M1 and M2 signature molecules are detected in L. donovani infected livers although they exhibit differences in their spatial distribution in infected tissues.